Incubation behavior adjustments, driven by ambient temperature variation, improve synchrony between hatch dates and caterpillar peak in a wild bird population - Simmonds, E; Sheldon, B; Coulson, T; Cole, E (John Wiley & Sons Ltd, 2017)
For organisms living in seasonal environments, synchronising the peak energetic demands of reproduction with peak food availability is a key challenge. Understanding the extent to which animals can adjust behaviour to optimise reproductive timing, and the cues they use to do this, is essential for predicting how they will respond to future climate change. In birds, the timing of peak energetic demand is largely determined by the timing of clutch initiation, however, considerable alterations can still occur once egg laying has begun. Here, we use a wild population of great tits (Parus major ) to quantify individual variation in different aspects of incubation behaviour (onset, duration and daily intensity), and conduct a comprehensive assessment of the causes and consequences of this variation. Using a 54-year dataset, we demonstrate that timing of hatching relative to peak prey abundance (synchrony) is a better predictor of reproductive success than clutch initiation or clutch completion timing, suggesting adjustments to reproductive timing via incubation are adaptive in this species. Using detailed in-nest temperature recordings, we found that post-laying, birds improved their synchrony with the food peak primarily by varying the onset of incubation, with duration changes playing a lesser role. We then used a sliding time window approach to explore which spring temperature cues best predict variance in each aspect of incubation behaviour. Variation in the onset of incubation correlated with mean temperatures just prior to laying, however incubation duration could not be explained by any of our temperature variables. Daily incubation intensity varied in response to daily maximum temperatures throughout incubation, suggesting female great tits respond to temperature cues even in late stages of incubation. Our results suggest that multiple aspects of the breeding cycle influence the final timing of peak energetic demand. Such adjustments could compensate, in part, for poor initial timing, which has significant fitness impacts.